ESRA19-0635 Should we use genicular nerve block for pain control after knee surgery?. (30th August 2019) - Krol, A; Vanneste, B; Tomlison, J; Desmet, M; Simpson, G
Abstract : Introduction knee osteoarthritis – epidemiology : Osteoarthritis (OA) is a natural occurrence in the elderly population. Symptomatic knee OA is present in 20–30% of the population aged >65 years and causes a significant burden on modern health systems. The prevalence of knee OA is rapidly increasing with prolonged life expectancy. Patients with mild symptoms can be initially managed with conservative treatments, such as physical therapy, nonsteroidal anti-inflammatory drugs (NSAIDs), intra-articular steroid, hyaluronic acid infiltration, viscous replacement, regenerative therapy such us prolotherapy and PRP (platelets rich plasma) or ablation of the sensory nerves supplying the anterior joint capsule. Total knee arthroplasty (TKA) is considered the most cost effective management for patients with advanced OA and moderate to severe symptoms who have failed conservative treatment. A survey of 18 countries with a total population of 755 million estimated 1, 324, 000 TKA annually, 175/100.000 population. 1 2 Pain management after TKA Fast track after TKA to minimize cost, maximize profit and facilitate patient experience without compromising safety and outcome has become gold standard. Anaesthesia and pain management for TKA has been the subject of scrutiny and has resulted in a plethora of publications. 3–5 Emphasis on early mobilization has created a challenge for perioperative pain management. Multimodal analgesia has been advocated to reduce side effects of large dose of any pain killers in monotherapies, chiefly opioids. In this manuscript the authors focus on various aspects of regional anaesthesia. Spinal anaesthesia has been, and still is at the core of intraoperative management. On the contrary continuous epidural analgesia for postoperative pain has declined in popularity. The risks and practicalities of epidural use such as abscess/hematoma, urinary retention, prolonged motor block affecting mobilisation and immediate rehabilitation as well as the logistics of care have made continuous epidural analgesia impractical, cumbersome and far from complication. Lumbosacral plexus block has similar limitations and unlike the brachial plexus is not easy accessed and blocked with a single injection.Selective nerves block: femoral, sciatic, obturator, lateral cutaneous nerve of thigh (LFCN) makes at least 4 injections limited by safe volumes of local anaesthetic and motor block after surgery can inevitable. Sciatic and femoral nerve blocks combined provide sufficient analgesia and still remains the gold standard in some centres. Prolonged motor block can be prevented by reduction in concentration and volume of local anaesthetic (LA) in most clinical situations. In the last decade focus on motor sparing blocks energised interest and 'rediscovered' human anatomy. Discussions sparked about the adductor canal (Hunter Canal – John Hunter was a surgeon at St George's Hospital in London -author's note) and the femoral triangle. 6 7 Whether blocking only the saphenous nerve selectively or jointly with branches to vastus medialis and posterior branch of obturator nerve, covering a larger area, but with potential motor weakness of vastus medialis, makes significant clinical differences open to debate. The aforementioned blocks cover only the anterio-medial part of the knee but are reproducible, safe, fast to perform and do contribute to multimodal analgesia. Completing analgesia around the knee also depends on the skill of surgeon. Local infiltration analgesia (LIA) of posterior knee capsule and periosteum as surgery progress may be very effective but requires meticulous technique. 8 Figure 1 demonstrates the technique of LIA by the operator. Fluoroscopy and ultrasound guided genicular nerves block/ablation in chronic pain C hronic pain physicians have developed an interest in blocking only the sensory nerves innervating anterior capsule of the knee joint – genicular nerves and then proceed to radiofrequency denervation or cryoablation. Choi et al. in double-blind randomized controlled trials described a simple yet elegant technique of fluoroscopy guided denervation of the superomedial, superolateral and inferomedial genicular nerves at the junction of the shaft and the epicondyle of the femur and tibia alike. 9 The inferolateral genicular nerve and recurrent articular branch both from common peroneal nerve (CPN) were deliberately omitted to avoid the risk of injury to CPN. Yet, ablation of only 3 nerves supplying anterior capsule provided at least 50% pain relief in 59%, 65%, and 59% of patients at 1, 4 and 12 weeks, respectively 9 . Soon after, ultrasound guided techniques have been described to position a needle at the same inflection point with close relation to the periosteum and genicular artery, however the genicular nerves themselves are not always visible. 10 11 Simple ultrasound guided technique has been described in A Pocket Guide to Ultrasound Guided Chronic Pain Interventions 13 : Place the probe in a longitudinal orientation on the lateral or medial aspect of the lower femur to identify the junction of the epiphysis and diaphysis Identify the genicular vessels in cross–section adjacent to the femur/tibia Rotate the probe 90 degrees into the transverse plane, along the junction of the femoral or tibial shaft and epicondyle. Insert the needle in–plane in an anterior to posterior direction Target the tip of the needle at the midpoint of the bone adjacent to the periosteum. Alternatively the needle can be inserted out of plane using the initial longitudinal view. Ensure the probe remains at the junction of the diaphysis and epiphysis when changing from a longitudinal to transverse probe position Consider techniques that may increase the size of any radiofrequency lesion due to anatomical variation of the nerve course or slight probe misposition. Nerves may be difficult/impossible to visualise and the technique relies on the identification of bony and vascular landmarks. figure 2 demonstrates live model, skeleton, ultrasound longitudinal, transverse and fluoroscopy images. What we have learnt about knee innervation from anatomical studies? There is no consensus in the literature on the number and origin of branches innervating the anterior knee capsule. Anatomical research thrives and Franco et al. performed dissection of 8 cadaveric knees and found 6 nerves supplying the anterior knee capsule: superolateral branch from the vastus lateralis, superomedial branch from the vastus medialis (NVM), middle branch from the vastus intermedius (NVI), inferomedial branch from the saphenous nerve and inferolateral (ILGN) and recurrent branch (RFN) from the common peroneal nerve. 13 Most recently Tran et al. meticulously dissected 15 knees finding at least 11 branches supplying anterior knee in 4 quadrants. Superolateral quadrant: Nerve to vastus lateralis (NVL), Nerve to Vastus Intermedius (NVI), Superolateral Genicular Nerve (SLGN) from sciatic or common fibular nerve (CFN) and articular branch from CFN. Inferolateral quadrant: ILGN and RFN, both from CFN. Superomedial Quadrant supplied by NVM, NVI and SMGN terminal branch of femoral nerve. Inferomedial quadrant supplied by IMGN, a branch of the tibial nerve and infrapatellar branch of saphenous nerve (IPBSN). 14 Regardless of the origin, geniculars nerves do run fairly consistently at the points verified by fluoroscopy and ultrasonography as confirmed by the author's recent dissections in figure 3 . Summary and future directions or are there any?: Fundamental questions remain: Should we use genicular nerves blocks for pain control after knee surgery? Currently only one study a case series by Gonzales-Sotel investigated the question and the results were similar to surgical infiltration under direct vision . 16 It would be up to operating team: surgeon and anaesthetist to decide who performs the block. The authors' would expect an RCT including a group having genicular nerve ablation prior TKA, compared with a control group (no intervention). Would there be a drop out and decline of surgical treatment after successful denervation? Would denervation prior the surgery affect postsurgical pain and its management? While the authors of this manuscript have been asking these question Waleda et al. published their data. Cooled RFA of the superior lateral, superior medial and inferomedial genicular nerves, performed 2–6 weeks prior to elective TKA as part of a multimodal postoperative pain management regime had no measurable effect on postoperative opioid use, analgesia use, or function in the 48 hours following surgery. In addition, no long term effect on outcome measures was found 1, 3 and 6 months after TKA. 17 Is this an end or beginning? References: Felson DT. An update on the pathogenesis and epidemiology of osteoarthritis. Radiol Clin North Am 2004;42:1–9. Garstang SV, Stitik TP. Osteoarthritis: epidemiology, risk factors, and pathophysiology. Am J Phys Med Rehabil 2006;85:S2–S14. Bendtsen TF, Moriggl B, Chan V, Borglum J. The optimal analgesic block for total knee arthroplasty. Reg Anesth Pain Med 2016;41:711–719. Boezaart AP, Parvataneni HK. Everybody knows that the dice are loaded: how can we block the nerves that innervate the knee joint without blocking the nerves that innervate that joint? Reg Anesth Pain Med 2016;41:665–666. Perlas A, Kirkham KR, Billing R, et al. The impact of analgesis modality on early ambulation following total knee arthroplasty. Reg Anesth Pain Med 2013;38:334–339. Jaeger P, Zarc D, Fromsgaard JS, et al. Adductor canal block versus femoral nerve block for analgesia after total knee arthroplasty: a randomized double -blind study. Reg Anesth Pain Med 2013;38:526–532. Bendtsen TF, Moriggl B, Chan V, Pendersen EM, Borglum J. Defining adductor canal block. Reg Anesth Pain Med 2014;39:253–254. Kerr DR, Kohan L. Local infiltration analgesia: a technique for the control of acute postoperative pain following knee and hip surgery: a case study of 325 patients. Acta Orthop 2008; 79:174–183. Choi WJ, Hwang SJ, Song JG, et al.: Radiofrequency treatment relieves chronic knee osteoarthritis pain: a double-blind randomized controlled trial. Pain 2011;152:481−487. Krol A, Nejad B, Tavakkoli-Zadeh M. Reg Anesth Pain Med 2015 Sep/Oct;40(5):Supplement 1. But M, Krol A. Reg Anesth Pain Med 2016 Sep/Oct;41(5):e1–e162. Simpson G, Krol A, Nicholls B, Silver D. A Pocket Guide to Ultrasound Guided Chronic Pain Interventions (ESRA in press). Franco CD, Buvanendran A, Petersohn JD, et al. Innervation of the Anterior Capsule of the Human Knee: Implications for Radiofrequency Ablation. Reg Anesth Pain Med 2015 Jul–Aug;40(4):363–8. Tran J, Peng PWH, Lam K, Baig E, Agur AMR, Gofeld M. Anatomical Study of the Innervation of Anterior Knee Joint Capsule: Implication for Image-Guided Intervention. Reg Anesth Pain Med 2018;43:407–414. Krol A. Ultrasound guided radiofrequency procedures in chronic pain management. Journal of Observational Pain Medicine 2015;1(5):22–28. González Sotelo V, Maculé F, Minguell J, Bergé R, Franco C, Sala-Blanch X. Ultrasound-guided genicular nerve block for pain control after total knee replacement: Preliminary case series and technical note. Rev Esp Anestesiol Reanim 2017 Dec;64(10):568–576. Walega D, McCormick Z, Manning D, Avram M. Radiofrequency ablation of genicular nerves prior to total knee replacement has no effect on postoperative pain outcomes: a prospective randomized sham-controlled trial with 6-month follow-up. Reg Anesth Pain Med 2019. April (ahead of print).